Rifaximin, a Nonabsorbed Oral Antibiotic, Prevents Shigellosis after Experimental Challenge - Taylor, David N.; McKenzie, Robin; Durbin, Anna; Carpenter, Colleen; Atzinger, Christophe B.; Haake, Robert; Bourgeois, A. Louis (Clinical infectious diseases, 2006)
Background. This double-blind, placebo-controlled study was conducted to assess the efficacy of the nonabsorbed oral antibiotic rifaximin to prevent shigellosis in volunteers challenged with Shigella flexneri. Methods. Volunteers were randomized to receive either prophylactic rifaximin (200 mg 3 times daily for 3 days; n = 15) or placebo (n = 10) on days 0, 1, and 2. On day 1, volunteers were challenged with ∼1500 colony-forming units of S. flexneri 2a strain 2457T given orally in sodium bicarbonate buffer. Results. The incidence of diarrhea was 0 with rifaximin, compared with 60% with placebo (P = .001). The median time to onset of diarrhea was 78.5 h with placebo (P < .001). The incidence of dysentery was 0 for rifaximin and 10% for placebo (P = .4). The incidence of colonization with Shigella was 0 with rifaximin, compared with 50% with placebo (P < .005). A significant serum or mucosal immune response after challenge by at least 1 indicator (immunoglobulin A titer, immunoglobulin G titer, and immunoglobulin A antibody—secreting cell count) was 0 with rifaximin and 80% with placebo (P < .001). Conclusions. Rifaximin was effective and well tolerated, compared with placebo, in preventing shigellosis in this double-blind study of volunteers challenged with S. flexneri 2a.